2016
DOI: 10.1038/onc.2016.336
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the proapoptotic protein MOAP-1 by the UBR5 ubiquitin ligase and its role in ovarian cancer resistance to cisplatin

Abstract: Evasion of apoptosis allows many cancers to resist chemotherapy. Apoptosis is mediated by the serial activation of caspase family proteins. These proteases are often activated upon the release of cytochrome c from the mitochondria, which is promoted by the proapoptotic Bcl-2 family protein, Bax. This function of Bax is enhanced by the MOAP-1 (modulator of apoptosis protein 1) protein in response to DNA damage. Previously, we reported that MOAP-1 is targeted for ubiquitylation and degradation by the APC/CCdh1 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 36 publications
3
65
0
1
Order By: Relevance
“…Matsuura et al . confirmed the sensitization to cisplatin upon UBR5 knockdown and showed that co-knockdown of MOAP-1 reduced the cisplatin sensitization effect of UBR5 knockdown, suggesting that UBR5 uses MOAP-1 in part to induce cisplatin resistance (3). Moreover, our lab showed that ectopic overexpression of UBR5, but not a UBR5 point mutant in which the critical cysteine required for its ubiquitin ligase activity was mutated, enhanced cisplatin resistance in cells (15), showing that overexpression of UBR5 alone was sufficient to induce cisplatin resistance, dependent upon its ability to ubiquitinate its substrates.…”
mentioning
confidence: 80%
See 4 more Smart Citations
“…Matsuura et al . confirmed the sensitization to cisplatin upon UBR5 knockdown and showed that co-knockdown of MOAP-1 reduced the cisplatin sensitization effect of UBR5 knockdown, suggesting that UBR5 uses MOAP-1 in part to induce cisplatin resistance (3). Moreover, our lab showed that ectopic overexpression of UBR5, but not a UBR5 point mutant in which the critical cysteine required for its ubiquitin ligase activity was mutated, enhanced cisplatin resistance in cells (15), showing that overexpression of UBR5 alone was sufficient to induce cisplatin resistance, dependent upon its ability to ubiquitinate its substrates.…”
mentioning
confidence: 80%
“…have discovered a novel mechanism of cisplatin resistance in ovarian cancer that works through destabilization of MOAP-1 (modulator of apoptosis 1), a protein with a BH3-like motif that stimulates activation of the pro-apoptotic Bcl-2 family protein Bax (2,3). MOAP-1 is an effector of the RASSF1A (Ras association domain family 1A) tumor suppressor that regulates extrinsic apoptosis through the TNFα (tumor necrosis factor α) and TRAIL (TNF-related apoptosis inducing ligand) pathways (4).…”
mentioning
confidence: 99%
See 3 more Smart Citations